2018
DOI: 10.1021/acs.jpcc.8b01377
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Stratified Diffusion of Water Inside Carbon Nanotubes; Direct Experimental Evidence with 2D DT2 NMR Spectroscopy

Abstract: Water, when confined at the nanoscale acquires extraordinary transport properties, and yet, there is no direct experimental evidence of these properties at nanoscale resolution. Here, by using two-dimensional NMR diffusion–relaxation (D–T 2) and spin–lattice – spin–spin relaxation (T 1–T 2) spectroscopy, we succeeded to resolve at the nanoscale water diffusion in single- and double-walled carbon nanotubes (SWCNTs/DWCNTs). In SWCNTs, the spectra display the characteristic shape of uniform water diffusion restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 41 publications
6
47
0
Order By: Relevance
“…This indicates the high fragility of water molecules in this system. The observed phenomena are consistent with the previous studies [ 26 , 27 , 41 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This indicates the high fragility of water molecules in this system. The observed phenomena are consistent with the previous studies [ 26 , 27 , 41 ].…”
Section: Resultssupporting
confidence: 94%
“…Recently [ 26 ], we addressed these issues using two-dimensional NMR diffusion- relaxation spectroscopy and we found that the water molecules inside the nano-tube resolve in two or more tubular components acquiring different-self diffusion constants ( D ) for a specific CNT diameter. Moreover, for the first time [ 27 ], we reported experimental results on the stratified water diffusion in CNTs and showed that water dynamics at the center of CNT exhibiting non-Arrhenius behavior, characterized by ultrafast diffusion and extraordinary fragility.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, experimental and theoretical effort has been spent in the description of the structure of nanotube water as a function of SWCNT diameter, [10][11][12][13] and a variety of experimental techniques, from X-ray diffraction (XRD) 14 and inelastic neutron scattering (INS) 9,10 to nuclear magnetic resonance (NMR), 15 have been exploited to explore this type of system.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have progressively advance our understanding of the electrical and mechanical properties of CNTs, as well as the nature and characteristics of water in the carbon nanotubes. In this context, the arsenal of experimental methods applied to the system at hand includes X-ray Compton scattering [ 36 , 37 ], transmission electron microscopy (TEM) [ 38 , 39 , 40 , 41 , 42 ], infrared [ 43 ], dielectric [ 44 ] and Raman [ 45 , 46 ] spectroscopies, thermogravimetric analysis [ 47 ] differential scanning calorimetry, dielectric relaxation spectroscopy, neutron diffraction and adsorption [ 48 ], as well as and nuclear magnetic resonance (NMR) [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. From a theoretical standpoint, molecular dynamics (MD) is the most common toolset utilized to study the properties of water in CNTs [ 4 , 22 , 30 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ,…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most important issue in regard to water in CNTs is defining the properties of its diffusion. It has been shown both theoretically [ 4 , 75 ] and experimentally [ 63 , 64 ] that under certain conditions the dimensional restriction and the water-wall interactions cause an enhanced diffusion coefficient for water in CNTs, compared to bulk water. In addition, if the CNT is narrow enough (d < 1 ), then water molecules cannot surpass each other any more, turning the dynamic process from the typical classical/Fickian diffusion to a single-file diffusion.…”
Section: Introductionmentioning
confidence: 99%